2003
DOI: 10.1038/sj.bjp.0705547
|View full text |Cite
|
Sign up to set email alerts
|

Hyper‐reactivity of cerebral arteries from ovariectomized rats: therapeutic benefit of tamoxifen

Abstract: 1 An increased incidence of systemic hypertension has been documented in postmenopausal women and identified as an independent risk factor in the development of cerebrovascular stroke. The present study examined whether cerebrovascular reactivity was increased in the hypertensive ovariectomized rat, and explored the potential therapeutic benefit of the partial estrogen receptor agonist tamoxifen. 2 Female Sprague -Dawley rats were subjected to bilateral ovariectomy (OVX, n ¼ 16) or a sham operation (n ¼ 8). At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…The class of compounds referred to as SERMs possess partial estrogen activity and mimic the beneficial effect of the endogenous hormone on bone resorption and circulating HDL levels [3,12,19]. In addition, TAM therapy normalized the exaggerated cerebral vascular reactivity to norepinephrine in ovariectomized female rats [29]. However, during the early phase of remodeling in post-MI female rats, TAM administration increased infarct size and the underlying mechanism may have been related in part to the attenuation of new vessel growth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The class of compounds referred to as SERMs possess partial estrogen activity and mimic the beneficial effect of the endogenous hormone on bone resorption and circulating HDL levels [3,12,19]. In addition, TAM therapy normalized the exaggerated cerebral vascular reactivity to norepinephrine in ovariectomized female rats [29]. However, during the early phase of remodeling in post-MI female rats, TAM administration increased infarct size and the underlying mechanism may have been related in part to the attenuation of new vessel growth.…”
Section: Discussionmentioning
confidence: 98%
“…To examine the effect of TAM, a dose of 10 mg kg −1 per day was added to standard rat chow (12-24 h postsurgery), and continued for a period of 3 weeks. The dose of TAM employed in the present study was previously shown to normalize the exaggerated cerebral artery response to norepinephrine in the ovariectomized female rat [29]. During the 3-week protocol, rats were weighed every 2 days to adjust dosage according to changes in body weight (BW).…”
Section: Methodsmentioning
confidence: 99%
“…25 Because responses to PE are similar in aortas from ER␤KO and WT male mice, 4 it would also appear that the observed defect is a characteristic of small arteries alone. Indeed, PE responses have also been shown to be similar in aortas from WT, ER␤KO, and ER␣KO female mice after OVX and 17␤-estradiol supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This was unlikely to be attributable to increased basal synthesis of endothelium-derived vasodilators because PE-, NE-, and U46619-induced constrictions were unaffected by inhibitors of NOS and COX. An increased basal tension after NOS inhibition in isolated small arteries has been attributed to the endogenous synthesis of ET-1, 41,42 and increased basal tension in response to NOS inhibitor in cerebral arteries from OVX rats was associated with hypertension, 25 which could be prevented by ET A inhibition. 43 Therefore, observed AR abnormality could theoretically be achieved through increased basal ET-1 synthesis, but this requires verification by further investigations.…”
Section: Potency Of the Agonists Used For Contractile Response In Femmentioning
confidence: 99%
“…Experiments were conducted on isolated arteries of 1–2 mm length and 150–200 µm diameter using a wire myograph as previously reported [12]. They were set up on a myograph with a resting tension of 80–100 mg and bathed in a physiological salt solution containing the following composition (m M ): NaCl, 119; KCl, 4.7; KH 2 PO 4 , 1.18; MgSO 4 , 1.17; NaHCO 3 , 1.17; CaCl 2 , 1.16; EDTA, 0.023; glucose, 10.…”
Section: Methodsmentioning
confidence: 99%